2011
DOI: 10.1111/j.1440-1789.2011.01264.x
|View full text |Cite
|
Sign up to set email alerts
|

Chondroma of the dural convexity: A case report and literature review

Abstract: Chondromas are unusual tumors that arise from the base of the skull and have a predilection for the spheno-ethmoidal region. Chondromas represent less than 0.5% of all intracranial tumors. In rare instances, these tumors originate from the dura mater of the convexity. Fewer than 30 cases of dural chondromas arising from the convexity or the falx are reported in the literature. In this study, we describe a new case of convexity chondroma. We discuss the radiological and histological features of this case and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…By comparison, about 20 cases of intracranial dural chondromas, arising from the convexity or the falx cerebri, have been reported in the literature. 1 Although various hypotheses regarding the origin of intracranial chondromas have been presented, the pathogenesis of the chondromas re-mains controversial. It has been suggested that intracranial chondromas develop from heterotopic chondrocytes, 15 are secondary to metaplasia of meningeal fibroblasts or perivascular mesenchymal tissues, 2,5 or are secondary to the cartilaginous activation of fibroblasts by trauma or inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…By comparison, about 20 cases of intracranial dural chondromas, arising from the convexity or the falx cerebri, have been reported in the literature. 1 Although various hypotheses regarding the origin of intracranial chondromas have been presented, the pathogenesis of the chondromas re-mains controversial. It has been suggested that intracranial chondromas develop from heterotopic chondrocytes, 15 are secondary to metaplasia of meningeal fibroblasts or perivascular mesenchymal tissues, 2,5 or are secondary to the cartilaginous activation of fibroblasts by trauma or inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…16 Meningeal chondromas are also rare and have been reported only as intracranial tumors. Although 20 cases of chondromas originating at the convexity of the dura mater have been described, 1 to the best of our knowledge, there has been no report of a meningeal chondroma located in the spine. The aim of our case report was to describe a case of intradural chondroma located in the cervical spine.…”
mentioning
confidence: 93%
“…[12,18] Although not pathognomonic, well-circumscribed solitary lesions with stippled calcification, a characteristic pattern of ring-like mild peripheral enhancement with central nonenhancing area; heterogeneously hyperintense appearance on T2-weighted imaging; absence of dural tail, hemorrhage, or cystic areas; and lack of tumor blush on angiography should suggest the radiological diagnosis of a chondroma. [15] Immunostaining reveals S100 positivity and absence of epithelial markers. [20] Histologically, the chondroma has a well-differentiated cartilaginous tissue surrounded by a delicate fibrous connective tissue capsule.…”
Section: Primary Spinal Extraosseous Cervical Chondroma In An Adultmentioning
confidence: 99%
“…[1,19] The differential diagnosis includes a mesenchymal chondrosarcoma, meningioma, schwannoma, hemangiopericytoma, solitary fibrous tumor, Ewing's sarcoma, and metastatic tumor. [15] The primary microscopic differential diagnosis is a well-differentiated chondrosarcoma. Bland chondrocytes with no evidence of multinucleation, mitotic activity, or pleomorphism are evident among copious chondroid matrices.…”
Section: Primary Spinal Extraosseous Cervical Chondroma In An Adultmentioning
confidence: 99%
“…Numerous chondrocytes without nuclear atypia and mitotic active events are distributed in the rich cartilage matrix. Irregularly shaped calcifications and cystic areas have generally been found (2,4). The postoperative pathological examination of our case is consistent with these pathological features that determine the diagnosis of chondroma.Neuroimaging is the main method to discover chondroma of dural convexity and falx.…”
Section: A B C D Ementioning
confidence: 99%